ANALYSIS OF THE RELATIONSHIP AMONG TRAINING, SKILLS AND CONTENTEMENT OF THE EMPLOYERS - Roman Teodora; Maxim Emil; Manolica Adriana (Annals of the University of Oradea: Economic Science, 2013)
Successful designing and implementation of the quality management system in an organization requires taking into account the requirements of all categories of natural persons or legal entities which have direct or indirect interests towards it. Efficiency and effectiveness of the actions carried out to meet the expectations of stakeholders shall be assessed by periodic measurements and analyses accomplished with appropriate tools for each category. Obtaining favourable results following the measurement of contentment does not put an end to the process of relationships with the customers and stakeholders. Implementation of the process will reveal new expectations and requirements that, in conjunction with the ones existing in the Organization and in order to improve the activity will lead to strategies and policies that are intended to contribute to the continuous improvement of the relations with stakeholders. Thus, based on previous researches undertaken internationally and nationally, we carried out two investigations which aimed to identify the employers` needs and requirements related to the quality of skills provided by universities to the higher education graduates, and measurement of their degree of adjustment to the specified or implied requirements. In our country, the studies on employers\' requirements have permanently concerned the universities. The problems identified are almost similar with those abroad, and the solutions offered by many studies have not provided the solving key but only at most an improvement of the situation. The labour market in Romania is not structured, and there is no nationwide program for its development, but nevertheless the universities must provide the workforce for the next 3, 4 or 5 years. The researches carried out for this purpose show that work experience is considered by employers as a main criterion, stronger than the grade of graduation or than the reputation of the university where they graduated from. A first research - the exploratory type – has aimed through investigation to identify the following issues: the importance placed by employers on the staff selection criteria; areas in which employers have difficulties in finding staff with higher qualifications; skills that the employers would like the University to focus on, preparing additionally the graduates in this respect, and the general level of contentment in terms of the educational services quality. A second research – both the descriptive and explanatory type – has provided information on: identifying the skills required from the higher education graduates; measuring the importance placed by employers on several groups of skills and competencies; estimating the levels of the skills achieved in some Romanian universities; contentment survey related to other services provided by the higher education institutions in Romania.